Experimental determination of phase equilibria at 900°C and liquidus surface in the Cu-Ni-Ti system - Jin B.; Lu X.; Liu S.; Huang D.; Du Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Phase equilibria at 900°C and the liquidus projection in the Ni-rich corner of the Cu-Ni-Ti ternary system were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), electron probe microanalysis (EPMA) and differential scanning calorimetry (DSC) on the annealed and as-cast alloys. For the isothermal section at 900 °C, the hightemperature ternary compound (τ5) reported in the literature was not observed but the corresponding low-temperature compound (τ6) was identified to be stable at this temperature. For the liquidus projection, the primary phase τ4 was experimentally determined for the first time, and the related solidification paths were identified through the experimental data on the as-cast alloys. One solid-state invariant reaction, NiTi + τ4 → τ1 + Ni3Ti at 1098.3°C and two ternary eutectic reactions, L → τ1 + τ4 + NiTi at 1126°C and L → τ1 + τ6 + fcc(Cu,Ni) at 1069.5°C were detected. Scheil reaction scheme was also presented accordingly. All obtained experimental results will provide reliable information for further thermodynamic optimization of the Cu-Ni-Ti ternary system.